Chebyshev polynomial approximation on a closed subset with unique limit point and analytic extension of functions - Dovgoshei, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We describe the domain of analyticity of a continuous function f in terms of the sequence of the best polynomial approximations of f on a compact set K(K ⊂ ℂ) and the sequence of norms of Chebyshev polynomials for K.